Investigation of unstable soil stabilized using fly-ash cement grouting - Jayasinghe K.; Anggraini V.; Syamsir A.; Nanda (IOP Publishing Ltd, 2023)
Additives; Disasters; Fly ash; Mixtures; Soil cement; Soils; Deep soils; Different proportions; Different soils; Fly ash cements; Fly ash mixtures; Standard Proctor test; Unconfined compressive strength; Weak soil; Compressive strength